Is body mass index associated with the incidence of endometriosis and the severity of dysmenorrhoea: a case–control study in China? - Qi Chen; Yifei Gao; Yunhui Tang; Luling Lin; Mingzhi Zhao; George Qiaoqi Chen; Shouzhen Chen (BMJ Open)
Objective Endometriosis is considered as a serious gynaecological disease in women at a reproductive age. Lower body mass index (BMI) is thought to be a risk factor. However, recent studies indicated that women with normal BMI were also more likely to develop endometriosis, suggesting the association with BMI is controversial. We therefore investigated the association of BMI and surgically diagnosed endometriosis in a cohort of Chinese women.Design Retrospective case–control study.Setting Tertiary hospital.Patients 709 women with endometriosis and 807 age matched controls between January 2018 and August 2019.Intervention Age at diagnosis, parity, gravida, BMI and self-reported dysmenorrhoea status were collected and the association of BMI and endometriosis was analysed.Measurement and main results Overall, the median BMI was not different between patients and controls (21.1 kg/m2 vs 20.9 kg/m2, p=0.223). According to the BMI categories for Asians/Chinese by WHO (underweight: <18.5 kg/m2, normal weight: 18.5–22.99 kg/m2, overweight: 23–27.49 kg/m2, obese: ≥27.50 kg/m2), overall, there was no difference in the association of BMI and endometriosis (p=0.112). 60% of patients were of normal weight. However, the OR of obese patients (BMI over 27.50 kg/m2) having endometriosis was1.979 (95% CI 1.15 to 3.52, p=0.0185), compared with women with normal weight. 50.3% patients reported dysmenorrhoea, and the OR of developing severe dysmenorrhoea in obese patients (BMI over 27.50 kg/m2) was 3.64 (95% CI 1.195 to 10.15, p=0.025), compared with patients with normal weight.Conclusion Our data demonstrate that overall there was no association between BMI and the incidence of endometriosis, but there was a significant increase in the incidence of endometriosis in obese women, compared with women with normal weight. Obesity was also a risk factor for severe dysmenorrhoea.